Antara Persepsi Peternak dan Keberhasilan Inseminasi Buatan (IB) dalam Upaya Percepatan Peningkatan Populasi Sapi - Ria Kusumaningrum (Institut Agama Islam Sahid (INAIS) Bogor, 2022)
Food security is an important issue for all countries in the world because it is related to the limitations in the fulfillment of food, energy and water due to an increase in population. Indonesia as a developing country has a problem in the level of food production and distribution which only supplies local resources. The Special Efforts Program for the Acceleration of Increasing Cattle Obligatory Populations (Upsus Siwab) is a national program for food security with the target of accelerating the increase in population of cattle. But in fact in 2018 there was a decline in cattle population in Indonesia which means that the Upsus Siwab program which was made a strategic step by the Ministry of Agriculture since 2017 has not been able to run according to the target. The causes of this program's failure will be examined in this article. The Upsus Siwab program reviewed focuses on improving Artificial Insemination (IB) services. The success rate of IB is influenced by several factors, namely the quality of frozen semen, human resources (inseminator and farmer), IB acceptor physiology, IB implementation time and livestock maintenance management. The critical success factors that have been anticipated in the Upsus Siwab program are the quality of frozen semen, human resources (inseminator) and the physiology of IB acceptors, while other determinants have not been resolved properly because they are directly related to the expertise and skills of the breeders themselves. Basically, farmers will breed their livestock, either in natural mating or IB. And when viewed from the side of farmers' perceptions of the implementation of IBs, it can be concluded that the knowledge and awareness of farmers in implementing IBs in Indonesia is good. This is evidenced that 47 percent of the cows population did IB before the Upsus Siwab program and when compared to the number of IB implementations after the program did not differ much there was only an increase of 12 percent. So it appears that the increase in the implementation of IB in this program is not proportional to the increase in the number of IB acceptors by 52 percent. This program can be modified with a counseling program for farmers in the form of animal husbandry management training and skills in determining heat. In addition, the target of implementing the Upsus Siwab program is not only seen from the number of IB acceptors but from the addition of the number of IB acceptors for farmers who have never done IB and/or farmers who do not yet have an awareness of the importance of IB.